The Significance of Internet Communication in Public Deliberation - Rasmussen, Terje (Javnost-The Public, 2009)
The article addresses recent structural changes in the public sphere related to media as platforms for debate and deliberation. New media platforms for communication lead to changes in the communication structure itself. This can easily be seen in the differentiation processes of the public sphere that is now taking place: The differentiation of topics, styles and actors is an astonishing phenomenon, is constantly a topic of debate in itself, often labelled as both decay and democratisation. I argue that as Internet- based media take actively part in, and accelerate the internal diff erentiation of the public sphere, the role and function of the public sphere is put in a new light. Inner divisions of labour in the public sphere emerge, which forces us to reconsider conventional understandings of the political public sphere vis-à-vis political deliberation. The article addresses this new complexity of public discourse and presents a revised view on its democratic functions. I argue that as a consequence of the Internet, social and political theory need to distinguish between a presentational and a representational dimension, each serving different functions. I also argue that the altered media composition underlying the public sphere suggests a more network-like view on national and international public spheres.